PENGARUH APLIKASI BERBAGAI MACAM PUPUK ORGANIK DAN KNO3 TERHADAP DIAMETER BUAH DAN DAYA SIMPAN BUAH STROBERI (Fragaria sp. Var. Mencir) - mabdan syakuro; Anis Sholihah; Nurhidayati Nurhidayati (AGRONISMA, 2022)
Strawberries (Fragaria sp var. Mencir) are a good source of vitamin C, in strawberries contains more vitamin C than citrus fruits. Strawberries contain high antioxidants because they contain quarcetin, ellagic acid, anthocyanins, and kaempferol. This factor is one of the reasons why strawberries are much in demand and consumed by the public. This study aims to determine the effect of the application of a combination organic fertilizers and KNO3 on the diameters and storage life of strawberry plants (Fragaria sp.var. mencir). This experiment is a pot experiment using a factorial randomized block design. Factor 1 is the type of organic fertilizer consisting in four kind, among: O1 = Cow Manure, O2 = Conventional Compost, O3 = Vermicompost, O4 = Nano Vermicompost. Factor 2 is the Concentration of Potassium Nitrate (KNO3) which consists of three levels, among: K0 = No KNO3 application, K1 = KNO3 2 g/l, K2 = KNO3 4 g/l. The results showed that the use of inorganic materials did not have a significant difference to organic materials.Â Key words : Strawberry, organic fertilizer, vermicompost, diameters and storage life.